Antineutrophil cytoplasmic antibody positivity in IgG4-related disease: A case report and review of the literature. Issue 34 (August 2016) - Della-Torre, Emanuel; Lanzillotta, Marco; Campochiaro, Corrado; Bozzalla, Emanuele; Bozzolo, Enrica; Bandiera, Alessandro; Bazzigaluppi, Elena; Canevari, Carla; Modorati, Giulio; Stone, John H.; Manfredi, Angelo; Doglioni, Claudio
Abstract: Background: IgG4-related disease (IgG4-RD) is a fibroinflammatory condition characterized by serum IgG4 elevation and tissue infiltration of IgG4-positive plasma cells. Substantial overlap between IgG4-RD and antineutrophil cytoplasmic antibodies (ANCA)-associated vasculitides (AAV) exists in terms of organ involvement and histopathological features. A positive ANCA assay is regarded as a highly specific finding in favor of an AAV, and generally influences away from a diagnosis of IgG4-RD. Recent reports, however, have raised the possibility that some patients with IgG4-RD are ANCA positive, thus suggesting reconsideration of the role of ANCA in the diagnostic workup. In the present work, we describe the first case of concomitant biopsy-proven IgG4-RD and granulomatosis with polyangiitis (GPA), demonstrating antiproteinase 3 (PR3) ANCA of the IgG4 subclass in the patient's serum. We also review the literature in order to provide clinicians with tools for interpreting ANCA positivity in IgG4-RD patients. Case summary: A 51-year-old woman was referred for left exopthalmos due to lacrimal gland enlargement and increased serum IgG4 concentration. IgG4-RD was suspected and further imaging studies disclosed multiple pulmonary masses in the right lung. Histological analysis of the left lacrimal gland was diagnostic for IgG4-RD, but lung biopsy showed typical features of GPA. ANCA assay was positive for anti-PR3 antibodies. Further immunofluorescence studies demonstrated anti-PR3 antibodies of IgG1 and IgG4 subclass. Treatment with rituximab induced swift remission of both IgG4-RD and GPA manifestations. We identified 9 other reports of patients with IgG4-RD and positive ANCA in the English literature, 5 cases with biopsy-proven IgG4-RD and 4 cases in whom IgG4-RD was diagnosed presumptively. Four patients had also histological evidence of concomitant AAV. Conclusion: The present work demonstrates that ANCA positivity in patients with biopsy-proven IgG4-RD should prompt the exclusion of a concomitant vasculitic process; a positive ANCA does not exclude the diagnosis of IgG4-RD; confirmation through immunoenzymatic assays of the ANCA specificity, clinical-pathological correlation, and histopathological evaluation remain crucial steps for the differential diagnosis between AAV and IgG4-RD.